apropos: Perspektiven auf 5 Jahre, und 10 Ausgaben und 155 Artikel - Behrens, Christoph; Kern, Beate; Laorden Albendea, María Teresa; Lehnert, Joris (apropos [Perspektiven auf die Romania], 2023)
Editorial